Role of TGFβ-activated cancer-associated fibroblasts in the resistance to checkpoint blockade immunotherapy - Hou, Weibin (Frontiers in Oncology, 2025)
Immune checkpoint blockers (ICBs) have revolutionized cancer treatment by enabling durable responses. However, most patients showed resistance and limited efficacy. Elucidating mechanisms of resistance is imperative to extend the clinical utility of ICBs. Emerging evidence highlights cancer-associated fibroblasts (CAFs), particularly TGFβ-activated myofibroblastic CAFs, as key orchestrators of immunosuppressive TMEs and ICBs resistance. These CAFs drive T-cell exclusion preventing intratumoral T cells from engaging cancer cells. This review explores the role of TGFβ signaling in CAFs in driving immune evasion and therapy resistance. While targeting TGFβ or CAFs directly has shown limited inconsistent results, downstream molecules in TGFβ-activated CAFs, including induced TGFβ (βig-h3), endocytic receptor 180 (Endo180), leucine-rich repeat containing 15 (LRRC15), and NADPH oxidase 4 (NOX4), emerge as promising therapeutic targets to counteract T-cell exclusion and restore immunotherapy sensitivity. Advancing research on CAF heterogeneity and pro-tumorigenic subsets may uncover innovative strategies to expand immunotherapy benefits.